The Effectiveness of Steeping Rosella (Hibiscus Sabdariffa) Against Hypertension in the Elderly - Tetty Rina Aritonang; Rupdi Lumban Siantar; Farida Mentalina Simanjuntak (International Journal of Science and Society, 2021)
In Indonesia, hypertension is the third leading cause of death, following only stroke and tuberculosis. It is a degenerative condition in the elderly, and with growing age, nearly all feel a rise in blood pressure. Taking an infusion of rosella flowers (Hibiscus sabdariffa Linn) in the morning and evening will reduce blood pressure. Contain phytochemicals that can help lower blood pressure. This study aims to see how successfully giving rosella flower infusion (hibiscus sabdariffa linn) against hypertension in the elderly at the Matraman District Health Center. The experimental one-group pre-and post-test configuration with control was used in the analysis. The sample size was 10 people and used comparative analysis with paired t-test using computerized statistical software. The results showed that the decrease in blood pressure using the infusion of rosella flowers was smaller than the amlodipine treatment. This indicates that steeping Rosella does not have a significant effect on hypertension.